1993
DOI: 10.1159/000227231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Doses of Intravenous Polyclonal IgG on in vivo Levels of 12 Pneumococcal Antibodies in Patients with Chronic Lymphocytic Leukaemia and Multiple Myeloma

Abstract: Polyclonal intravenous IgG (IVIG) was administered as an infusion 6 times every 3 weeks (weekO, 3, 6, 9, 12, 15) in doses of 0.1, 0.4 and 0.8 g/kg BW to determine the dose causing an increase in 12 pneumococcal antibody types above the protective level of 200 ng/ml of antibody N. The dose of 0.4 g/kg BW was found to be optimal in patients with chronic lymphocytic leukaemia (CLL). From the first infusion onwards at least 80% of CLL patients had increases in all 12 antibodies. Five weeks after the last infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 9 publications
(16 reference statements)
1
24
0
1
Order By: Relevance
“…Similar results have been observed in dose evaluation studies in secondary immunodeficiency disorders, suggesting the need for regular medical evaluation of patients 20,41 .…”
Section: Dose and Administrationsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar results have been observed in dose evaluation studies in secondary immunodeficiency disorders, suggesting the need for regular medical evaluation of patients 20,41 .…”
Section: Dose and Administrationsupporting
confidence: 81%
“…In studies examining ivig, the initial dose has ranged from 100 mg/kg to 800 mg/kg or a total dose of 10-24 g per infusion. The study by Sklenar et al 41 found the ideal dose to be 400 mg/kg every 3 weeks until a steady state is reached, followed by a maintenance dose of 400 mg/kg every 5 weeks. However, the study by Boughton et al 20 that used a dose of 18 g every 3 weeks found that, by increasing the dose in patients with breakthrough infections, 50% were kept infection-free.…”
Section: Dose and Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous immunoglobulin was found to be effective at reducing the incidence of bacterial infections [23][24][25][26], although no effect on overall mortality has been reported [27]. A starting dose of 400 mg/kg every 3 weeks was suggested [28]; however, evidence in the context of CLL [29] and primary antibody deficiencies [30] suggests that the dose may need to be altered in individual patients with the aim of preventing breakthrough infections and progression of structural lung disease. Although the cost-effectiveness of replacement immunoglobulin has previously been questioned in this setting [31], it is likely that rigorous patient selection, the increasing use of subcutaneous immunoglobulin in home therapy programmes and improved patient survival will have altered the cost-benefit ratio, although this remains to be formally assessed [21 & ].…”
Section: Key Pointsmentioning
confidence: 99%
“…In a similar approach, oseltamivir prophylaxis given for 12 weeks has been shown to reduce culture-or PCR-confirmed influenza infection in solid organ and SCT recipients [80]. Finally, patients with hypogammaglobulinemia such as CLL or myeloma patients, and especially those who do not respond to vaccines, may benefit from immune globulines [81,82].…”
Section: Compliance To Immunization Guidelines In the Oncology Wardmentioning
confidence: 99%